Prevalence and Determinants of Home Delivery among Indigenous Women in an Aspirational District of Meghalaya, India - Shylla, Badondor; Dolkar, Tshering; Upreti, Binu; Shullai, Wansalan Karu (National Journal of Community Medicine, 2026)
Background: In Meghalaya, India, the tribal population faces significant barriers that contribute to lower rates of facility-based births. The aim was to assess the prevalence and determinants of home deliveries in Meghalaya. Methodology: This community-based cross-sectional study, conducted in an aspirational district of Meghalaya between August 2023 - July 2024. 360 mothers who delivered in the past 12 months were enrolled through a multistage sampling technique. SPSS version 27.0 was used for data analysis, employing bivariate logistic regression with a significance level set at p <0.05. Results: In this study, 130 (36.1%) of mothers delivered at home, with two-thirds of these deliveries conducted by unskilled birth attendants. Women with two to four children (AOR = 0.09), five or more children (AOR = 0.05), and those living over 5 kilometres from a health facility (AOR = 0.42) were less inclined to utilize institutional delivery services. While the odds for institutional delivery were higher among mothers who attended ≥ 4 antenatal care visits (AOR = 2.97) and those satisfied with ANC services (AOR = 13.96). Conclusions: The findings underscore the importance of improving access to quality antenatal care and addressing geographical barriers to improve regional institutional delivery rates.